The Manifestation of Wahdatul Adyan in Ibn Arabi's Perspective as a Basis of Religious Moderation in Indonesia - Miftakhur Rohman; Abdulloh Hanif (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2026)
Indonesia's profound religious, ethnic, and cultural diversity necessitates a robust framework for religious moderation to maintain national unity. However, public misunderstanding persists, particularly the erroneous equation of moderation with the claim that